The effect of Matricaria chamomilla extract on the fungi isolated from the upper respiratory tract - H. Hady, Douaa; A. Khairalla, Inass; Abdul-Majeed, Khulood; Jafeer, M. (Al-Qadisiyah Journal of Pure Science, 2018)
The results of the current study showed that the fungus isolated from patients with upper respiratory tract that Cladosporium spp fungi highest percemtage contamination of43 %, while Aspergillus terrus fungus record lowest contamination of 4.4% and the study showed inhibitory effect of aqueous extracts hot plant Matricaria chamomilla inhibition. concentration used (25 , 50, 75 and 100) mg / ml on some pathogenic fung. ratio shown 100 % for fungi Penicillum spp at concentrations 75 and 100 mg / ml and the rate of diameter of the colonialy yeast Candida albicans inhabition concentration of 75 mg / ml was one cm , the fungus Cladosporium spp in concentrations of 25 and 50 mg / ml did not give any resistance to the extract.